KAUSALITAS DALAM NOVEL LELAKI HARIMAU KARYA EKA KURNIAWAN - Ibnu Yustiya Ramadhan (Prasasti: Journal of Linguistics, 2020)
In Eka Kurniawan’s novel, Lelaki Harimau, incoherent story telling is one of its most visible characteristeristic. Incohorent story telling is used by Eka kurniawan not only to pique the reader interest but also to emphasise cause and effect in every action that characters do in the novel. With a theory offered by Genette, this study tries to explain the order of event in Lelaki Harimau to show the causality that Eka Kruniawan use as the core theme in his novel. This study also tries to show how structural theories can be used as a foundation to interpret novel. From the explanation of causality in Lelaki Harimau novel, it is found that violence only begets violence.